Adhesive properties of water-washed cottonseed meal on four types of wood. Issue 19 (1st October 2016) - He, Zhongqi; Chapital, Dorselyn C.; Cheng, H.N.; Modesto, Olanya O.
Abstract: The interest in natural product-based wood adhesives has been steadily increasing due to the environmental and sustainable concerns of petroleum-based adhesives. In this work, we reported our research on the utilization of water-washed cottonseed meal (WCM) as wood adhesives. The adhesive strength and water resistance of WCM adhesive preparations on poplar, Douglas fir, walnut, and white oak wood veneers were tested with press temperatures of 80, 100, and 130 °C. Our data indicated that raising the hot press temperature from 80 to 100–130 °C greatly increased the bonding strength and water resistance of the WCM adhesives. The general trend of the adhesive strength of WCM on the four wood species was Douglas fir > poplar ≈ white oak > walnut. The rough surface of Douglas fir with tipping features could enhance the mechanical interlocking between the wood fibers and adhesive slurry, contributing to the high adhesive strength. The dimensional swelling of the bonded wood pairs due to water soaking was in the order: thickness > width (i.e. perpendicular to the wood grain) > length (i.e. parallel to the wood grain). The greatest dimensional changes were observed in Douglas fir specimens. However, the highest decrease in adhesive strength by water soaking was with poplar wood specimens. These observations suggested that the wood dimensional changes were not dominant factors on water weakening the bonding strength of these wood pairs.